"Coming Out" as a family with an LGB member in Japan: Normalizing strategies and negotiating with social norms. Issue 2 (3rd July 2019) - Motoyama, Kotona
ABSTRACT: Research on parents of an LGB child demonstrates the processes of parents' emotional and behavioral changes leading them finally to accept their children. Only after parents accept their children will they be able to start their own process of "coming out". This article examines how families with an LGB member in Japan come out by negotiating with social norms. Interviews with family members in Japan revealed that most respondents went through emotional and behavioral changes to accept an LGB member; however, their struggle continued even after they accepted an LGB member due to their fear of negative judgments by others around them. Also, the respondents felt more difficulty coming out to people they know than to anonymous others. How the respondents try to control their emotions and negotiate with others reveals that families face difficulties dealing with one of their members being an LGB person and coming out to others despite social improvements surrounding the LGB community in general. This shows that a certain degree of stigma against sexual minorities at the interpersonal level remains strong in the society. In response, respondents used a normalizing strategy in order to avoid possible conflicts with people in close relationships.